Intravitreal bevacizumab in diabetic retinopathy. Recommendations from the Pan-American Collaborative Retina Study Group (PACORES): The 2016 knobloch lecture (2018)
The advent of intravitreal anti-vascular endothelial growth factor (anti-VEGF) medications has revolutionized the treatment of diabetic eye diseases. Herein, we report the outcomes of clinical studies carried out by the Pan-American Collaborative Retina Study Group (PACORES), with a specific focus on the efficacy of intravitreal bevacizumab in the management of diabetic macular edema and proliferative diabetic retinopathy. We will also discuss the use of intravitreal bevaci-zumab as a preoperative, adjuvant therapy before vitrectomy for prolif-erative diabetic retinopathy. Copyright © 2017 by Asia Pacific Academy of Ophthalmology.